Media and the making of modern Germany mass communications, society, and politics from the Empire to the Third Reich - Ross, Corey, 1969- (Oxford University Press, 2008)
'Media and the Making of Modern Germany' provides a full account of the expansion of the mass media in Germany up to the Second World War, examining how the rise of film, radio, recorded music, popular press, and advertising fitted into the wider development of social, political, and cultural life.